2014
DOI: 10.1186/1476-511x-13-128
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypercholesterolemia and cardiac function evaluated by speckle tracking echocardiography in a rabbit model

Abstract: BackgroundAlthough hypercholesterolemia is a major risk factor for coronary artery disease (CAD), only limited data are available regarding its direct effect on myocardial function apart from CAD. The aim of this study was to evaluate LV systolic function using speckle-tracking echocardiography and investigate the relationship between hypercholesterolemia and myocardial function.MethodsTwenty-eight rabbits were randomly divided into three groups: 8 were fed normal chow for 3 months (group 1) and the remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Animal models have linked cholesterol levels with changes in both diastolic and systolic performance [ 22 , 23 ] and one study found an association with LV ejection fraction and HDL-cholesterol in patients with angina pectoris [ 24 ]. In a recent paper, Mochizuki et al [ 25 ] studied the clinical features of decreased GLS in 144 patients with diabetes and found that among others hypertriglyceridemia was closely associated with low GLS.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have linked cholesterol levels with changes in both diastolic and systolic performance [ 22 , 23 ] and one study found an association with LV ejection fraction and HDL-cholesterol in patients with angina pectoris [ 24 ]. In a recent paper, Mochizuki et al [ 25 ] studied the clinical features of decreased GLS in 144 patients with diabetes and found that among others hypertriglyceridemia was closely associated with low GLS.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin . The cardioprotective effect of the dietary flavonoid quercetin (found in many fruits, vegetables, leaves, and grains) against ischemia/reperfusion injury is well studied [ 159 163 ]; however, few studies are available in the literature regarding the impact on hypercholesterolemia-induced oxidative stress in the heart. It was reported that quercetin ameliorates left ventricular function, collagen deposition, and inflammatory cell infiltration in rats with metabolic syndrome [ 164 ].…”
Section: Modulation Of Hypercholesterolemia-induced Oxidative/nitrmentioning
confidence: 99%
“…After 10 weeks of cholesterol feeding, both systolic and diastolic impairments were detected without hypertrophy or elevated blood pressure in rabbits (Huang et al, 2004). Reduced myocardial strain was detected with speckle tracking echocardiography in rabbit after 2-and 3-month atherogenic feeding, without atherosclerosis (Liu et al, 2014). It was shown in a hypercholesterolemic rat model that sterol esters affect membrane composition, increase erythrocyte osmotic fragility and decrease antioxidant enzyme levels (Sengupta and Ghosh, 2014).…”
Section: Discussionmentioning
confidence: 99%